2010
DOI: 10.1159/000312813
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Management of Phenylketonuria

Abstract: Phenylketonuria (PKU) is caused by deficient activity of the enzyme phenylalanine hydroxylase, needed to convert the essential amino acid (AA) phenylalanine (phe) to tyrosine. In order to prevent neurological damage, lifelong adherence to a low-phe diet that is restricted in natural foods and requires ingestion of a phe-free AA formula to meet protein needs is required. The goal of nutritional management for those with PKU is to maintain plasma phe concentrations that support optimal growth, development, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
135
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 120 publications
1
135
0
8
Order By: Relevance
“…The primary therapy for PKU is life-long adherence to a diet that limits phe intake to the minimum amount needed to support growth and protein turnover (40). The low-phe PKU diet requires extensive restriction of foods containing natural protein (often only 5-10 g protein per day are allowed) and supplementation with amino acids (AA), usually in the form of a formula, to achieve adequate intake of nitrogen, indispensable AA, and micronutrients (31). Compliance with the low-phe diet is often poor after 10 yr of age, despite the detrimental neuropsychological consequences of hyperphenylalanemia (23,57).…”
mentioning
confidence: 99%
“…The primary therapy for PKU is life-long adherence to a diet that limits phe intake to the minimum amount needed to support growth and protein turnover (40). The low-phe PKU diet requires extensive restriction of foods containing natural protein (often only 5-10 g protein per day are allowed) and supplementation with amino acids (AA), usually in the form of a formula, to achieve adequate intake of nitrogen, indispensable AA, and micronutrients (31). Compliance with the low-phe diet is often poor after 10 yr of age, despite the detrimental neuropsychological consequences of hyperphenylalanemia (23,57).…”
mentioning
confidence: 99%
“…They also found that the non-defective version of the gene produces enzymes necessary for metabolizing phenylalanine, an amino acid toxic to neurons at high doses. A diet with limited phenylalanine, supplemental amino acids, and other nutrients prevents phenylalanine from accumulating and killing young children (Macleod & Ney, 2010), even though the genetic defect remains.…”
Section: Child Development and The Missing Linkmentioning
confidence: 99%
“…The acknowledged mainstream treatment for PKU patients is a strict Phe-restricted diet supplemented by a medical formula containing amino acids and other nutrients (63). However, the treatment for PKU is variable among different countries.…”
Section: Treatment For Pkumentioning
confidence: 99%